Sangue de Lua: reflexôes sobre espíritos e eclipses - Carlos Fausto (Journal de la Société des Américanistes)
Moon’s blood: reflections on spirits and eclipses. In 2003, the author witnessed a partial eclipse of the moon in the Kuikuro village of Ipatse (Upper Xingu, Brazil), which was followed by a series of ritual actions. These activities were documented by a team of Indigenous film-makers who produced a documentary video about the event. Taking this ethnographic and cinematographic experience as his starting point, the author reflects on the meaning of the eclipse for the Kuikuro, focusing on the explicit cosmological knowledge conveyed by them, on the nature of their adherence to a belief system, and on some mytho-ritual themes that, lacking a native exegesis, can only be understood through a comparative perspective.